Descriptive study of maternal outcomes in a near-miss cohort at Kagadi District Hospital, Uganda - Suuna, Micheal (Division of Emergency Medicine, 2017)
Background: An understanding of pregnancy related morbidity (obstetric near miss) provides valuable information that can be used in reduction of maternal mortality. This study aims to (i) Describe the prevalence and short term outcomes of obstetric near misses (ii) Evaluate the level of care through comparative analysis of obstetric near misses and maternal mortality in Kagadi district hospital, Uganda Methods: A facility based retrospective review of obstetric near miss cases and maternal deaths that occurred between 1st January 2015 and 31st December 2015. Obstetric near miss case definition was based on disease-specific criteria including: haemorrhage, hypertensive disorders of pregnancy, dystocia, infection and anaemia. Main outcome measures included the frequency of near-miss in each disease specific group, duration of hospital stay and maternal death. Secondary outcome measures included distribution of referral categories, caesarean section rate, hysterectomy and foetal outcomes measures i.e live births, still births, abortions, neonatal deaths. A comparative analysis of obstetric near miss and maternal mortality was done to determine the maternal near miss incidence ratio (MNMR), maternal mortality ratio (MMR) and Mortality indices. The maternal near miss to mortality ratio for the period of study was calculated. Results: There were 7169 admissions to the maternity ward with 4366 deliveries, 752 near misses and 12 maternal deaths. The prevalence of maternal near misses was 10.7%. Maternal near miss and maternal mortality ratio were 177.1 per 1000 and 282 per 100,000 live births respectively. The near miss to mortality ratio was 63:1. Dystocia (69.3%) was the most common near miss event, followed by haemorrhage (19.5%), infection (5.2%), anaemia (4.5%) and hypertension (1.5%). The mortality indices were 27.3%, 4.1%, 2.9%, 2.5% and 0.2% for hypertension, haemorrhage, anaemia, infection and dystocia respectively. Most complications developed at home (46.7%) while 36.5% and 16.5% occurred at the study site and other public facilities respectively. The mean duration of hospital stay was 3.6 days. The caesarean section rate was 12% of all hospital deliveries and 6 near misses had hysterectomy. Foetal outcomes were 78.4%, 14.2%, 5.6% and 1.8% for live births, abortions, fresh still births and neonatal deaths respectively. Conclusion: There is a high occurrence of near miss events at the health facility. Dystocia is the leading cause of obstetric near miss but hypertension and haemorrhage are associated with poor maternal outcome. Although most obstetric complications develop at home, a comparative analysis of morbidity and mortality at the health facility shows substandard care. In order to improve the quality of care there is need for advocacy for hospital delivery, development evidence management based protocols and routine audit of near miss.